Law Enforcement of Defaults in Intellectual Property Rights as Digital Trade Objects - Muhdar, Muhdar; Tohari, Mohamad; Suryandari, Wieke Dewi (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
The rise of information technology has highlighted the significance of Intellectual Property Rights (IPR), which protect creative efforts and economic investments. In the digital era, intellectual property rights have become a key means to support innovation, creativity, and healthy competition. This study aims to provide a comprehensive analysis and understanding of how to enforce laws regarding breaches of contract in the context of IPR within digital trade. The research contributes to the development of robust legal frameworks and practices in the digital economy. The research method used to write this is normative legal research method, which is legal research carried out by examining library materials and secondary data, where the approach used will be a normative juridical (statute approach) with descriptive-analytical character (Soerjowinoto, 2006). The normative approach is used to analyze Law Number 28 of 2014 concerning Intellectual Property rights and civil law, carried out through examining specific regulations or written laws related to the concept of law enforcement concerning intellectual property Rights as objects of digital trade.